Experiential Marketing's Impact on Visit Decisions: The Role of Visitor Satisfaction at Ullen Sentalu Museum - Yesa Ramadhani (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
This study aims to determine the effect of experiential marketing on visiting decisions through visitor satisfaction as an intervening variable (Case Study at the Ullen Sentalu Museum in Yogyakarta). The research methodology used uses quantitative methods. The population in this study is the population used is tourists who visit the Yogyakarta Ullen Sentalu Museum as many as 100 people. The sample used was 100 respondents using the Accidental sampling technique, which is a sample search based on chance, that is, anyone found by the researcher can be used as a sample, if it is deemed that the person met by chance is suitable as a data source. Methods of data analysis using Path Analysis (Path Analysis). The results of the study show that: (1) sense experience has a significant positive effect on the decision to visit the Ullen Sentalu Museum, Yogyakarta. (2) sense experience has a significant positive effect on visitor satisfaction and the decision to visit the Ullen Sentalu Museum, Yogyakarta. (3) experiencing a significant positive effect on the decision to visit the Ullen Sentalu Museum, Yogyakarta. (4) experience experience has a significant positive effect on visitor satisfaction and the decision to visit the Ullen Sentalu Museum, Yogyakarta. (5) think experience has a significant positive effect on the decision to visit the Ullen Sentalu Museum, Yogyakarta. (6) think experience has a significant positive effect on visitor satisfaction and the decision to visit the Ullen Sentalu Museum, Yogyakarta. (7) act experience has a significant positive effect on the decision to visit the Ullen Sentalu Museum, Yogyakarta. (8) act experience has a significant positive effect on visitor satisfaction and the decision to visit the Ullen Sentalu Museum, Yogyakarta. (9) linking experience to a significant positive effect on the decision to visit the Ullen Sentalu Museum, Yogyakarta. (10) associated experience with a significant positive effect on visitor satisfaction and the decision to visit the Ullen Sentalu Museum, Yogyakarta